THE EFFECT OF INFORMATION TECHNOLOGY USE AND VILLAGE OFFICE COMPETENCE ON THE PREVENTION OF VILLAGE FINANCIAL MANAGEMENT FRAUD WITH MODERATION OF INTERNAL CONTROL EFFECTIVENESS IN VILLAGE GOVERNMENTS IN DELI SERDANG REGENCY - Eka Nurmala Sari; Dewi Ladesye Napitupulu; Prawidya Hariani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study was to determine and analyze the influence of information technology utilization and village official competence on the prevention of fraud in village financial management, moderated by the effectiveness of internal control. It is suspected that information technology utilization and village official competence influence fraud prevention and moderate the effectiveness of internal control. This study used a quantitative approach with an associative approach. Data collection used primary data and a Likert-scale questionnaire distributed to village officials in Deli Serdang Regency, North Sumatra. The population consisted of 380 villages, and a sample of 79 villages, each represented by two financial managers, totaling 158 individuals. The sampling technique used was stratified random sampling. The data were processed using the SEM method with the aid of the Smart PLS analysis tool. The results of this study prove that the use of information technology has an effect on fraud prevention and that the competence of village officials has an effect on fraud prevention. The effectiveness of internal control cannot moderate the influence of the use of information technology and the competence of village officials on fraud prevention.